Effect of Fat Replacement with Tahena on the Quality Properties of Shortened Cake - Baghdad Science Journal (مجلة بغداد للعلوم)
The objective of this research was to investigate the effect of replacing fat(shortening) with different percentages of tahena on the quality properties (physiochemical and sensory ) of shortened cake.The percentages of moisture,protein ,fat and ash of cake increased significantly(p